2011
DOI: 10.1074/jbc.m110.201665
|View full text |Cite
|
Sign up to set email alerts
|

Collagen Fragments Inhibit Hyaluronan Synthesis in Skin Fibroblasts in Response to Ultraviolet B (UVB)

Abstract: UVB irradiation causes characteristic features of skin aging including remodeling of the dermal extracellular matrix. A key feature during this process is the up-regulation of matrix metalloproteinases and cleavage of collagen. Hyaluronic acid (HA), a major component of the dermal matrix, decreases after chronic UVB exposure. However, the factors that govern the decline of HA synthesis during the course of actinic aging are largely unknown. The aim of the present study was to explore whether collagen degradati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
68
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(75 citation statements)
references
References 57 publications
4
68
0
3
Order By: Relevance
“…Taken together, these results for HAS expression seem to indicate that the expression of HAS, especially HAS2, at both the gene and protein levels, mainly reflects the secretion levels of HA. These results are consistent with another study using UVB-exposed skin fibroblasts, which demonstrated that HAS2 is the predominant isoform expressed in skin fibroblasts and the extent of HAS2 down-regulation correlated with the UVB-induced decrease of HA secretion (Röck et al 2011).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Taken together, these results for HAS expression seem to indicate that the expression of HAS, especially HAS2, at both the gene and protein levels, mainly reflects the secretion levels of HA. These results are consistent with another study using UVB-exposed skin fibroblasts, which demonstrated that HAS2 is the predominant isoform expressed in skin fibroblasts and the extent of HAS2 down-regulation correlated with the UVB-induced decrease of HA secretion (Röck et al 2011).…”
Section: Discussionsupporting
confidence: 82%
“…In relation to the age-dependent impairment in wound healing, aging fibroblasts have a defect in their phenotypic maturation that is required for tissue remodeling and the closure of wounds because of the dysfunction of HA-dependent CD44/epidermal growth factor receptor signaling. The cellular mechanisms of UVB-induced changes in HA in skin cells and tissues have been studied in detail (Südel et al 2005;Averbeck et al 2006;Dai et al 2007;Röck et al 2011), and it has been shown that the loss of HA is closely associated with phenotypic characteristics of skin photo-aging (Margelin et al 1996;Takahashi et al 1995Takahashi et al , 1996. In contrast, the effects of chronological aging on HA are much less well understood.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a series of reports from the Fischer group (42) demonstrated that chronic UVB exposure caused a significant loss of HA from the dermis of mouse skin and decreased gene expression of all three HAS enzymes in the dermis. The UVB-induced down-regulation of Has2 was mediated by the activation of ␣ V ␤ 3 -integrin induced by collagen fragments (18). Another group reported that a single UVB exposure caused an increase in chondroitin sulfate but not in other glycosaminoglycans, including HA, in human skin (43).…”
Section: Discussionmentioning
confidence: 99%
“…Studies from different groups have shown that HAS2 plays a predominant role in inducible HA synthesis in fibroblasts exposed to growth factors (15,16), including fibroblasts undergoing transformation to myofibroblasts (17). Furthermore, down-regulation of Has2 gene expression is responsible for the inhibition of HA synthesis in skin fibroblasts in response to certain environmental stressors, such as UVB irradiation (18). The activity of HAS enzymes can be regulated at the transcriptional level (15,16,19,20) or at the posttranslational level by phosphorylation (21), OGlcNAcylation (22), or ubiquitination (23).…”
mentioning
confidence: 99%
“…Also, amplified AP-1 transcription induced collagen degradation by upregulating MMPs production in both fibroblasts and damaged keratinocytes [9] . Moreover, although UVB had short wave lengths, about 5% of UVB rays could reach dermal papillae and affect dermal fibroblasts [46] . Coinciding, degenerated fibroblasts were detected in the photoaged subgroup of the present study.…”
Section: Discussionmentioning
confidence: 99%